Assessment of drought tolerant ability and cloning of the encoding dehydrin protein (Lea-D11) giene of some mountain local soybean cultivars [Glycine max (L.) Merrill] - Mau, Chu Hoang; Hien, Nguyen Thu (Academia Journal of Biology, 2014)
Soybean [Glycine max (L.) Merrill] is a cultivar which has not only highly economic and nutritious value but also degraded earth- improved ability. The mountain local cultivars in the North of Vietnam are precious gene source because of preeminent quality and ability against the harm of environment. In our work, the artificial method of making drought is used to estimate the drought tolerant ability of nine mountain local soybean cultivars by physiological and biochemical aspects. Its result shows that there are four most drought tolerant soybean cultivars, which are CB4, VMK, QH and HL. The CB4, VMK and HL have the highest drought tolerant index (corresponding to 10633.87, 7198.52 and 6038.47) and the strongest increase of 200% of proline content (corresponding to 203.91, 208.28, 246,90% and 290.29%). A 751 bp dehydrin gene fragment from DNA of genome of seven local soybean cultivars was amplified by PCR with primers MD1, MD2 and carried out successfully the cloning of giene and determine the giene arrangement encoding dehydrin protein of VMK and CB4 which have the most drought tolerant ability. The nucleotide sequence of dehydrin gene of VMK and CB4 was compared with that of other 34 gene in GenBank, especially compared with that of four soybean cultivars (M103, CucVang, MV1C and V74). This shows that the dehydrin gene sequence and the amino acid sequence of these soybean cultivars have quite high homology. The dehydrin gene sequence of the VMK and CB4 has the homology of 99.9%, the amino acid sequence of the VMK and CB4 has the homology of 100%.